Search for B0→π0π0 decay - Asner, D; Eppich, A; Hill, T; Morrison, R; Briere, R; Chen, G; Ferguson, T; Vogel, H; Gritsan, A; Alexander, J; Baker, R; Bebek, C; et al. (2002)
We have searched for the charmless hadronic decay of B0 mesons into two neutral pions. Using 9.13 fb-1 taken at the Υ(4S) with the CLEO detector, we obtain an improved upper limit for the branching fraction B(B0→π0π0)<5.7 ×10-6 at the 90% confidence level.